2007
DOI: 10.3748/wjg.v13.i4.538
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with adenosine and adenosine A1 receptor agonist protects against intestinal ischemia-reperfusion injury in rat

Abstract: AIM:To examine the effects of adenosine and A1 receptor activation on reperfusion-induced small intestinal injury. METHODS:Rats were randomized into groups with sham operation, ischemia and reperfusion, and systemic treatments with either adenosine or 2-chloro-N 6 -cyclopentyladenosine, A1 receptor agonist or 8-cyclopentyl-1,3-dipropylxanthine, A1 receptor antagonist, plus adenosine before ischemia. Following reperfusion, contractions of ileum segments in response to KCl, carbachol and substance P were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Some studies have shown that A1 receptor mediates cholinergic nerve activity in ileum and the impaired cholinergic neurotransmission may mediate altered motility during inflammation (33,67,130). One study has demonstrated a beneficial effect of A1 receptor agonist in ischemic intestinal injury (103). As more information regarding the underlying physiology of the A1 receptors is gathered, further studies are required to define its role in intestinal inflammation if therapeutic targets are to be developed.…”
Section: A1 Receptormentioning
confidence: 98%
“…Some studies have shown that A1 receptor mediates cholinergic nerve activity in ileum and the impaired cholinergic neurotransmission may mediate altered motility during inflammation (33,67,130). One study has demonstrated a beneficial effect of A1 receptor agonist in ischemic intestinal injury (103). As more information regarding the underlying physiology of the A1 receptors is gathered, further studies are required to define its role in intestinal inflammation if therapeutic targets are to be developed.…”
Section: A1 Receptormentioning
confidence: 98%
“…However, adenosine is effective in protecting the intestinal microvasculature from the injurious effects of ischemia-reperfusion (Grisham et al, 1989), perhaps via A 1 receptors (Özaçmak and Sayan, 2007). It was concluded in another study that adenosine acts by modulating the inflammatory response evoked by intestinal reperfusion (Kaminski and Proctor, 1992).…”
Section: H Intestinal Vesselsmentioning
confidence: 99%
“…There is evidence for an anti-inflammatory role for A 1 R in lung 5 , liver 15 , kidney 16 , heart 17 , intestine 18 and skeletal muscle. 19 However, other studies have suggested that A 1 R antagonism has beneficial effects in lung and heart IR models.…”
Section: Discussionmentioning
confidence: 99%